DOES LONELINESS CAUSE INCREASED HEALTH AND SOCIAL CARE SERVICE USE BY OLDER PEOPLE? AN EVALUATION OF THE EVIDENCE. (11th November 2018) - Victor, C
Abstract: Loneliness in later life in the UK is generating a moral panic because of the consequences for the health and social care system of the increased demand generated by lonely older people. Loneliness for older people has been linked with increased use of primary care services, attendance at accident and emergency units, admission to acute hospitals and admissions to care homes. A comprehensive literature review identified 9 papers that reported service use for both lonely and not lonely people aged 50+ in Canada, the USA, Sweden, Singapore and Britain. Studies looked at the use of primary care, emergency department, hospital in-patient admissions and nursing home admissions and were generally small scale, use self-reported service use outcomes and are cross-sectional in design. Limitations in our current evidence base which do not support the extravagant claims made for the consequences of loneliness, in terms of service use, and subsequent costs.